Construction of a register-based severity index for anorexia nervosa in Denmark: Association with overall and cause-specific mortality - Janne Tidselbak Larsen; Hannah Chatwin; Zi-Ping Zhang; Loa Clausen; Cynthia Marie Bulik; Laura Marie Thornton; Nadia Micali; Liselotte Vogdrup Petersen; Zeynep Yilmaz (European Psychiatry)
Abstract